2018
DOI: 10.1029/2018jd028603
|View full text |Cite
|
Sign up to set email alerts
|

Retrievals of Riming and Snow Density From Vertically Pointing Doppler Radars

Abstract: Retrievals of ice and snow are made from Ka‐ and W‐band zenith‐pointing Doppler radars at Hyytiälä, Finland, during the snow experiment component of the Biogenic Aerosols: Effects on Clouds and Climate (2014) field campaign. In a novel optimal estimation retrieval, mean Doppler velocity is exploited to retrieve a density factor parameter, which modulates the mass, shape, terminal velocity, and backscatter cross sections of ice particles. In a case study including aggregate snow and graupel we find that snow ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
115
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(128 citation statements)
references
References 96 publications
5
115
0
Order By: Relevance
“…These relations were applied in the validation of ice cloud and precipitation retrieval algorithms. For example, the performance of the "unified" algorithm that combines the radar and lidar observations of EarthCARE, in a variety of snowfall conditions (Moisseev et al, 2017;Li et al, 2018), was tested using the snowfall data as 720 shown in Mason et al (2018;. Using these studies showed that the measurements collected at Hyytiälä, namely combined observations of the surface snowfall observations and multi-frequency radar observations, are ideally suited for verification of satellite cloud and precipitation retrieval algorithms.…”
Section: Satellite Data Validationmentioning
confidence: 99%
“…These relations were applied in the validation of ice cloud and precipitation retrieval algorithms. For example, the performance of the "unified" algorithm that combines the radar and lidar observations of EarthCARE, in a variety of snowfall conditions (Moisseev et al, 2017;Li et al, 2018), was tested using the snowfall data as 720 shown in Mason et al (2018;. Using these studies showed that the measurements collected at Hyytiälä, namely combined observations of the surface snowfall observations and multi-frequency radar observations, are ideally suited for verification of satellite cloud and precipitation retrieval algorithms.…”
Section: Satellite Data Validationmentioning
confidence: 99%
“…Szyrmer and Zawadzki, 2014a;Petäjä et al, 2016). Doppler velocity measurements of the terminal fallspeed of snow have been used to constrain variations in particle density by which riming of snow, and the mixed-phase cloud in which it occurs, can be diagnosed (Mosimann, 1995; 20 Szyrmer and Zawadzki, 2014a, b;Mason et al, 2018). Variations in the density of ice particles are also related to changes in their shape and structure-whether due to aggregation, riming or a combination of processes-which are reflected in their radar backscatter cross-sections (Leinonen and Szyrmer, 2015).…”
mentioning
confidence: 99%
“…Variations in the density of ice particles are also related to changes in their shape and structure-whether due to aggregation, riming or a combination of processes-which are reflected in their radar backscatter cross-sections (Leinonen and Szyrmer, 2015). Mason et al (2018) formulated a single parameter modulating the density, shape and structure of ice particles which was retrieved in single-and dual-frequency Doppler radar retrievals, and was chiefly constrained by the mean Doppler velocity. This representation was based on a large database of ice particle mass-25 and area-size relations and insights from remote-sensed and in-situ measurements of snow events (Kneifel et al, 2015), but it remains to explore in more detail how the parameters controlling the size distribution and morphology of snow particles relate to one another and their radar scattering characteristics.…”
mentioning
confidence: 99%
See 2 more Smart Citations